The Dilemma of Autonomy : Decentralization and Water Politics at the Sub-National Level - Moore, Scott M. (Taylor and Francis, 2017)
This article develops a framework for understanding the role of subnational states in water politics in decentralized federal systems. First, that role has increased worldwide as a result of decentralization. Second, the quest for autonomy sometimes leads subnational officials to prefer weak forms of cooperation. Third, the interaction of subnational states, central governments and non-governmental actors largely explains interjurisdictional conflict and cooperation in shared river basins. This framework is applied to the case of the Colorado River basin to help explain a long-term shift towards more cooperative relationships between the riparian states.